EP691 Does apronectomy improve outcomes for the morbidly obese patient undergoing gynae cancer surgery? A review of four cases. (1st November 2019) - Addley, S; Sinclair, S; Dobbs, S; McComiskey, M; Glenn, D
Abstract : Introduction/Background: For the morbidly obese patient undergoing laparotomy and pelvic clearance in the context of an oestrogen-driven gynae cancer, concomitant apronectomy confers multiple benefits - optimising intra-operative pelvic access; improving post-operative recovery and general health; as well as also having the potential to reduce future peripheral oestrogen production, with positive implications for cancer recurrence. Methodology: The aim was to describe the short-term outcomes of performing apronectomy at the time of laparotomy for gynae malignancy in the morbidly obese patient. A retrospective case-note review of morbidly obese patients undergoing apronectomy as a component of gynae cancer surgery between 2017 and 2019 in a district general hospital in Northern Ireland was performed. Results: Four patients were identified, with mean age 56 years and mean BMI 53 kg/m 2 . Three patients were undergoing laparotomy for endometrial adenocarcinoma, and the fourth for suspected ovarian malignancy. At each surgery, the operating team consisted of a minimum of three Consultants: one gynae-oncologist, one gynaecologist and one plastic surgeon. No anaesthetic complications occurred. Each patient received intra-operative antibiotic prophylaxis and underwent TAH, BSO, omentectomy/omental biopsy and apronectomy with re-siting of the umbilicus. The average weight of apron excised was 9.6 kg. Each patient had two negative-pressure wound drains placed. Skin was closed with monofilament sutures and negative-pressure dressings applied. No intra-operative complications occurred, the maximum blood loss was 300 mls and mean operating time 217 minutes. One patient required HDU for 24 hours. Immediate post-operative complications included anaemia (50%); wound infection/partial dehiscence (50%); one case of return to theatre for debridement of a non-viable umbilicus; paralytic ileus (25%); and urinary tract infection (25%). The mean length of stay was 16 days. In the 30 day post-operative period, one patient was readmitted with wound infection. Conclusion: Overall, apronectomy appears to be a safe addition to laparotomy in this challenging patient population. Disclosure: Nothing to disclose.